A comparative assessment of the municipal solid waste management services - Ayuba, Kadafa Adati; Abd Manaf, Latifah; Abdullah, Sabrina J. Ho; Sulaiman, Wan Nor Azmin (Marsland Press, 2013)
Mankind naturally depends on the environment to sustain their lives but solid waste is one of the three major environmental problems in Nigeria, Malaysia and many other developing and even the developed countries are threatened by this. Waste management generally plays a significant role in the ability of nature to sustain life within its capacity and therefore an integral part of urban and environmental management in every city. Currently municipal solid waste management is a globally challenging issue especially in developing countries, due to its adverse environmental effects. This research is a comparative study aimed at rating municipal solid waste management services in FCT Abuja and Putrajaya towards identifying deficient areas requiring improvements. Residential questionnaire were used for the assessment. The data obtained was analyzed using qualitative and quantitative methods; specifically descriptive, parametric and nonparametric statistics.